Labour market regulation and foreign direct investment: US multinationals in Germany and the UK - Kerstin Pull (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2002)
At a time of intensifying uncertainty, managerial flexibility to adapt to changes in the economic environment is increasingly important. Different business loca-tions, it is frequently argued, offer this flexibility to differing degrees, and labour market regulations are held to be one essential factor in determining the resulting attractiveness of a country as a business location. This paper takes an options perspective in order to grasp the potential effect of labour market regulations on location decisions. The option value of an investment, it is argued, is influenced, among other factors, by labour market regulations. Depending on their prefer-ence for certain options, different investors will prefer different labour market settings. The ability of the options perspective to assess the role of labour market regulations for the attractiveness of international business locations is exempli-fied by a British-German comparison and then confronted with secondary data as well as with a unique data set derived from a survey of US multinationals in the UK and Germany.
Keywords: F23; J53; 330; labour market regulation; location decision; option value of flexibility